Felda settlers' perceptions towards integrated pest management (IPM) practices / Nur Masriyah Hamzah ...[et al.] - Hamzah, Nur Masriyah; Mohamad Razali, Raznilazim; Rosli, Fazidah; T Abu Bakar, Tengku Halimatun Sa'adiah (Universiti Teknologi MARA Cawangan Pahang, 2021)
Despite the rapid growth of the oil palm industry in Malaysia, the oil palm remains prone to the threat by a variety of insect pests. The practice of Integrated Pest Management (IPM) among oil palm growers in Malaysia helps to remove the overdependence on pesticides thus making the process more sustainable. The objectives of this study were to understand the FELDA settlers' perceptions of IPM practices, to determine the types of IPM practices being used by the settlers, and to identify the constraints affecting the adoption of IPM practices. The study was conducted with randomly selected 204 FELDA settlers in Jengka, Pahang, Malaysia. The results revealed that 91% of respondents were unfamiliar with the terms and meaning of IPM, 54% perceived IPM implementation might increase management costs and 98% of settlers reported that they constantly used resistant crops and occasionally identified insect pests in their plantation. Lack of exposure to IPM techniques, requiring discipline and schedules to follow, and lack of support by the government and statutory body were the major constraints reported by the settlers. Conclusively, the settlers' knowledge and attitudes towards the use of pesticides in accordance with the principles of IPM can be increased more effectively in the future.